Jump-Starting Urban Rat Research: Conspecific Pheromones Recruit Wild Rats into a Behavioral and Pathogen-Monitoring Assay - Parsons, Michael H.; Sarno, Ronald J.; Deutsch, Michael A. (Frontiers in Ecology and Evolution, 2015)
Wild rats, Rattus spp, have adapted so well to urbanization that humans may be obligatory to their survival. Consequently, rats foul human food sources, predate threatened fauna and serve as reservoirs for disease, costing the US economy $19 billion in losses year -1. Urban rat ecology however, remains vastly unexplored because these animals are cryptic, crepuscular, difficult to identify, and hazardous to handle. Additionally, the high-rise buildings that block satellite link-ups, underground sewers and subway tunnels, and rebar enforced concrete covered landscape make it difficult—if not impossible— to track urban animals using traditional radio telemetry. Consequently, there are few ecological studies with free-ranging urban rats. Therefore, we set out to monitor the behaviors and health of free-ranging rats in metropolitan New York. Recognizing that wild rats are attracted to live laboratory-reared conspecifics and that they are sensitive to pheromones, we used soiled rat bedding to repeatedly attract animals to a Remote Frequency Identification (RFID)- based antenna with camera-trap and load cell (scale) for collecting weights. We captured and micro-chipped 13 rats within 50, 30 and 10 m from our antenna and followed their movements. Seven of the 8 animals released within 10 m of the antenna, visited the RFID antenna lure 398 times over 41 standardized days. Males (2.7 visits day-1) visited the antenna at the same frequency as females (2.7 visits day-1; P>0.5), and both sexes spent similar time dwelling at the pheromones (M, 2.9±0.9 sec; F, 2.4.±0.4 sec; P>0.05). The passive integrated transponder (PIT)-tag worked free on the lone individual that did not participate. Within our population, female activity peaked between 6am and 7pm, while males visited throughout the day. Our results demonstrate the potential to safely overcome the primary barriers that have impeded urban rat ecological studies. We used pheromone-based lures to attract micro-chipped rats, irrespective of sex or age-class, where their individual identities, behaviors and pathogen loads could be consistently recorded. We discuss the potential for similar assays to help address several longstanding knowledge gaps in the literature regarding pathogen monitoring over time and space, rat dispersal patterns, population parameters and seasonal migrations through corridors.